Pedagogical practices of sustainability and society course delivery in higher education - Kalthom Husain,; Puziah Abd Wahab,; Haniza Othman,; Mohamad Nor Hisyam Musa,; Hafizul Amin Ngatli, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sustainability education prepares learners to comprehend the complex issues that situates in the community. Higher institutions are building and shaping students with ecosystems. The call for the need of education policies to be (re)oriented towards social change, sustainability and preparing students for life in a global society. This area of pedagogy is not free from problem. When policy is turned into practice instructors in higher education need to take a number of factors into account, especially when global sustainability issues are complex. This research was motivated from the issue that sustainability is perhaps best understood as an emerging paradigm that involves shifting to holistic, systemic, connective and ecological ways of thinking and learning. In accordance to that statement, the present research aims at engaging life experience on pedagogical practices which include approaches and methods from four instructors who had experience in teaching sustainability and society course at Albukhary International University, a private philanthropy higher institution. The instructors or academics from varied disciplines and teaching experience were invited to articulated different ways of enacting pedagogies related to their teaching. The research adopts qualitative approach via focus group interview to gather the desired data. The data was analysed using thematic analysis. There were three themes identified of which one is an emerging theme. It includes tips in teaching sustainability and society, the approaches and methods. The conclusion is that these instructors’ experiences can help us to understand this work and how it can provide some useful insights in pedagogical concerns.